A review of the therapeutic uses of thrombin - Lundblad, Roger L.; Bradshaw, Ralph A.; Gabriel, Don; Ortel, Thomas L.; Lawson, Jeffrey; Mann, Kenneth G. (Thrombosis and Haemostasis, 2004)
Thrombin is the product of the hemostatic response essential to the conversion of fibrinogen to fibrin. In addition, it is also responsible for the aggregation of blood platelets in the formation of the “platelet plug” as well as the activation of factor VIII, factor V, factor XI, factor XIII and protein C. The action of thrombin is not confined to the hemostatic response as it also has a critical function in the wound healing process by stimulating ‘mitogenic’ events through interaction with cell surface receptors. In this review, we consider the various biological activities of thrombin as they relate to current therapeutic use. While there has been considerable interest in the development of fibrin sealant products, there has been considerably less interest in documenting the continuing use of thrombin as a therapeutic. The use of thrombin for topical hemostasis and the treatment of pseudoaneurysms will be discussed in detail. It is concluded that the use of thrombin as a drug will not only continue but also will significantly increase. However, the availability of a safe human thrombin preparation will be critical for the continued use of thrombin as a therapeutic.
Keywords: Pseudoaneurysms; vascular surgery; thrombin; topical hemostatic agents; interventional radiology